Bilik-Bilik Demokrasi dalam Pendidikan - Mukodi, Mukodi (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
Not only having state and nation that requires democratic civility, but education also urgently requires fundamental democratic principles. The democracy is principled with transparency, participation, tolerance, openness of thought and diversity of ideas. Also with education, taking apart in culture and being naturally with it. The realization of the democratic education constructs academic maturation process. Lastly, it has impact on the building of the tolerant and humanist individual; that finally, realizing the leading Indonesian generation who ready to compete in the global world arena. The realization also have to be pursued through the contestation of the real democracy education.Bukan hanya bernegara dan berbangsa yang membutuhkan keadaban demokrasi, akan tetapi pendidikan pun sangat membutuhkan prinsip-prinsip demokrasi yang asasi. Demokrasi berprinsipkan transparansi, partisipatif, toleransi, keterbukaan pemikiran, dan keragaman ide serta gagasan. Pun demikian halnya dengan pendidikan, meretas kultur dan alaminya dengan hal itu. Terwujudnya pendidikan demokratis menjadikan proses pematangan akademik. Ujungnya, berdampak pada terbentuknya manusia toleran, dan humanis. Muara akhirnya, mewujudkan generasi Indonesia yang handal dan siap berkompetisi dalam percaturan dunia global. Perwujudannya pun harus diupayakan melalui ruang kontestasi pendidikan demokrasi yang sesungguhnya.